The SWELL1 Channel Promotes Ischemic Brain Damage by Mediating Neuronal Swelling and Glutamate Toxicity - Jianan Chen; Junhua Yang; Jiachen Chu; Kevin Hong Chen; Jesse Alt; Rana Rais; Zhaozhu Qiu (Advanced Science)
Abstract Cytotoxic neuronal swelling and glutamate excitotoxicity are two hallmarks of ischemic stroke. However, the underlying molecular mechanisms are not well understood. Here, it is reported that SWELL1, the essential subunit of the volume‐regulated anion channel (VRAC), plays a dual role in ischemic injury by promoting neuronal swelling and glutamate excitotoxicity. SWELL1 expression is upregulated in neurons and astrocytes after experimental stroke in mice. The neuronal SWELL1 channel is activated by intracellular hypertonicity, leading to Cl− influx‐dependent cytotoxic neuronal swelling and subsequent cell death. Additionally, the SWELL1 channel in astrocytes mediates pathological glutamate release, indicated by increases in neuronal slow inward current frequency and tonic NMDAR current. Pharmacologically, targeting VRAC with a new inhibitor, an FDA‐approved drug Dicumarol, attenuated cytotoxic neuronal swelling and cell death, reduced astrocytic glutamate release, and provided significant neuroprotection in mice when administered either before or after ischemia. Therefore, these findings uncover the pleiotropic effects of the SWELL1 channel in neurons and astrocytes in the pathogenesis of ischemic stroke and provide proof of concept for therapeutically targeting it in this disease.